1987
DOI: 10.1111/1540-6229.00428
|View full text |Cite
|
Sign up to set email alerts
|

An Approach to Industrial Real Estate Market Segmentation and Valuation Using the Arbitrage Pricing Paradigm

Abstract: This paper investigates whether a segmented market exists for industrial real estate with respect to risk and return characteristics. Given the existence of industrial market segmentation, the next issue examined is whether a submarket perspective or an integrated real estate market orientation provides better rate of return estimates for individual industrial properties using an Arbitrage Pricing Theory (APT) framework. The results support the existence of regional markets for industrial real estate. A submar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(20 citation statements)
references
References 31 publications
0
20
0
Order By: Relevance
“…For a comparison of holdings-based and returns-based allocation analysis, seeChristopherson (1995) andTrzcinka (1995). Also seeMyer and Webb (2000), who perform property attribution tests on a sample of REITs; andGallo et al (1997), who perform similar tests on mortgage-backed security funds.23 Grissom, Hartzell and Liu (1987) were among the first to discuss the impact of geographic regions on real estate prices.24 Prior to performing the attribution analysis, we regressed market-adjusted CREF returns (CREF return minus NPI return) against the regional indices. Slopes from the regression measure differences in asset class exposures between the CREF portfolio and the NPI.…”
mentioning
confidence: 99%
“…For a comparison of holdings-based and returns-based allocation analysis, seeChristopherson (1995) andTrzcinka (1995). Also seeMyer and Webb (2000), who perform property attribution tests on a sample of REITs; andGallo et al (1997), who perform similar tests on mortgage-backed security funds.23 Grissom, Hartzell and Liu (1987) were among the first to discuss the impact of geographic regions on real estate prices.24 Prior to performing the attribution analysis, we regressed market-adjusted CREF returns (CREF return minus NPI return) against the regional indices. Slopes from the regression measure differences in asset class exposures between the CREF portfolio and the NPI.…”
mentioning
confidence: 99%
“…The empirical results show the income capitalization rate of the 12 metropolitan areas significantly varied. Many research studies suggested cap rates of different locations or submarkets in the metropolitan areas may have different space factors (Grissom et al, 1987;Hartzell et al, 1987;Saderion et al, 1994;Sirmans et al, 1996). Gunnelin et al (2004) found that suburban areas have higher discount rates and vacancy rates, and lower market rent.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A handful of older studies, have analysed the distinguishing characteristics of the industrial property sector: Grissom et al (1987), investigate whether segmented market exists for industrial real estate with respect to the risk and return characteristics. The results support the existence of segmented markets for industrial real estate.…”
Section: Unit Root Testsmentioning
confidence: 99%